Combined nandrolone and resistance training induced cardiac remodelling and oxidative stress despite enhanced cardiomyocyte contractility - Alexa Alves de Moraes; Pedro Zavagli Suarez; Arthur Eduardo de Carvalho Quintão; Beatriz Lana Fontes; Sebastião Felipe Ferreira Costa; Carolina Camargos Rocha; Leôncio Lopes Soares; Luciano Bernardes Leite; Leandro Licursi de Oliveira; Emily Correna Carlo Reis; Edilamar Menezes de Oliveira; Pedro Forte; et al. (PLoS ONE, 2026)
Background Nandrolone decanoate (ND) is widely used by individuals engaged in resistance training (RT), yet their combined effects on cardiac function remain unclear. Objective To investigate the effects of RT and ND on cardiac structure and function, cellular contractility, Ca² ⁺ -handling protein expression, and redox balance in rats. Methods Thirty-two male Wistar rats were assigned to four groups: control (C), trained (C-T), ND (N), and trained ND (N-T). Animals received ND or saline for eight weeks, and RT was performed 3 × /week. Cardiac function was assessed by echocardiography, and isolated cardiomyocytes from the left and right ventricles (LV and RV) were evaluated for contractile function. Protein expression of Ca² ⁺ -handling regulators and oxidative stress markers was quantified. Results N-T increased LV and RV diameters by 25% and 33%, septal thickness by 41.7%, and reduced ejection fraction by 12.3% compared to N (p < 0.05). LV cardiomyocytes increased width by 29% and volume by 23% in N-T versus C-T (p ≤ 0.04). In LV, N-T showed greater contraction amplitude and velocity at 5 Hz (p = 0.04) and increased relaxation velocity at 1, 3, and 5 Hz (p < 0.01), with shorter time to peak contraction and 50% relaxation at 1 Hz versus N (p = 0.04). In RV, N-T increased contraction amplitude and velocity at 1 and 5 Hz, reduced time to peak at 1 and 3 Hz, shortened relaxation time at 1 Hz, and showed higher relaxation velocity than N and C-T (p < 0.02). Molecular analyses revealed reduced RyR2 expression (25% in LV and 9% in RV) and a 41% decrease in LV phospholamban in N-T versus C-T (p < 0.05). N-T also exhibited higher LV malondialdehyde compared to C-T (p = 0.03). Conclusion ND combined with RT induced adverse cardiac remodeling and impaired ventricular function, despite enhanced cardiomyocyte contractility, and intensified molecular and oxidative disturbances, indicating a maladaptive cardiac response. This is the first study to demonstrate regional differences in contractility and redox balance of isolated ventricular cardiomyocytes under ND plus RT.